Comparative diagnostic and prognostic implications of right versus left bundle branch block in patients with suspected ST-segment elevation myocardial infarction. (3rd October 2022) - Soerensen, N A; Fakhri, Y; Gossling, A; Neumann, J T; Haller, P M; Toprak, B; Lehmacher, J; Twerenbold, R; Westermann, D; Andersson, H; Jensen, L O; Holmvang, L; et al.
Abstract: Background: Current ESC guidelines on management of acute myocardial infarction in patients presenting with ST-segment elevation (STEMI) recommend emergent invasive management in patients with ischemic symptoms and bundle branch block (BBB). While left bundle branch block (LBBB) is a well-known high-risk feature in patients with acute myocardial infarction, data on the diagnostic and prognostic impact of right bundle branch block (RBBB) in comparison to LBBB in the context of STEMI are scarce. Methods: A prospective cohort of 2, 139 patients with suspected STEMI were triaged by the on-call cardiologist to acute coronary angiography based on a prehospital, tele-transmitted digital 12-lead electrocardiogram. All discharge diagnoses were independently adjudicated. The diagnostic accuracy of RBBB or LBBB was calculated. 30-day and 1-year all-cause mortality were from a central national registry and compared for LBBB, RBBB and patients without BBB using the Kaplan Meier method. Unadjusted and adjusted (age, sex, hypertension, hyperlipoproteinemia, smoking status and history of coronary artery disease) hazard ratios for 1-year mortality were calculated for both BBB-types. Results: The final diagnosis of STEMI was adjudicated in 1, 832/2, 139 (85.6%) of patients. RBBB was present in 117 (5.5%), LBBB in 61 (2.9%) patients, respectively. Patients with BBB were older than non-BBB patients: Median age was 69.7 years in RBBB, 68.9 years in LBBB and 62.6 years in non-BBB patients. Comparing both BBB types, LBBB patients more often had prior heart failure (6.3% in RBBB vs 11.5% in LBBB), while RBBB patients more often developed cardiac arrest before angiography (15.3% vs 3.7% in RBBB and LBBB patients respectively) and more frequently revealed Thrombolysis in Myocardial Infarction (TIMI) grade flow of 0 (61.0% vs 47.2%, respectively). Specificity for the final diagnosis of STEMI was not significantly different in both BBB-types: 95.1% (95% CI 92.1–97.0) in RBBB versus 92.8% (95% CI 89.4–95.2) in LBBB patients (p=0.25). Patients with RBBB had significantly higher 30-day and 1-year mortality (Figure 1), while LBBB and non-BBB patients showed similar outcome. Unadjusted hazard ratio for 1-year mortality comparing RBBB to non-BBB patients was 3.35 (95% CI 2.11–5.34, p<0.001) and 1.4 (95% CI 0.57–3.44, p=0.46) when comparing LBBB to non-BBB patients. After adjustment hazard ratio for RBBB patients was 2.3 (95% CI 1.25–4.21, p=0.007). Conclusion: In the context of suspected STEMI, RBBB is an ominous sign associated with adverse clinical features like cardiac arrest prior to PCI, TIMI grade 0 flow, compared to LBBB or non-BBB presenters. Consequently, RBBB patients had poorer outcome after 12 months. Our data therefore reinforce current guidelines in designating RBBB-patients as very high-risk, demanding immediate management and triage. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Regional Research Foundation in Region Sjaelland, Denmark